Miss Hickory - Bailey, Carolyn Sherwin, 1875-1961.; Gannett, Ruth Chrisman, 1896-1979 (New York : Vikings Press, 1946)
Relates the adventures of a country doll made of an apple-wood twig with a hickory nut for a head.
Crow makes a call -- Moon before snowfall -- Up McIntosh lane -- Squirrel finds a live nut -- Miss Hickory' good deed -- Barn news -- Runaway fawn -- Wild-heifer's supper party -- Now Christmas comes -- Ground hog sees his shadow -- Miss Hickory takes to the air -- Bull frog loses his clothes -- Homeless again -- Squirrel takes revenge -- Anything can happen.
"First published ... in September 1946."
870L
Accelerated Reader
Mode of access: Internet.
Newbery Medal, 1947
Keywords: Newbery Medal; Dolls -- Fiction; Dolls; Country life; Poupées -- Romans, nouvelles, etc. pour la jeunesse; Country life -- Fiction; Dolls -- Fiction; Country life -- Juvenile fiction; Dolls -- Juvenile fiction; New Hampshire; New Hampshire -- Romans, nouvelles, etc; New Hampshire -- Fiction; Fantasy fiction; Fantasy fiction; Juvenile works; Fiction; Adventure stories; Fantasy fiction; Juvenile books; Adventure stories